Pelatihan Pemulasaraan Jenazah Berbasis Majelis Taklim sebagai Upaya Regenerasi dan Pemberdayaan Masyarakat di Kecamatan Parung - Ro'is Amin; Bilqis Naufi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The corpse care program in Parung District, Bogor Regency, is a collaborative initiative between extension officers from the Parung Office of Religious Affairs (KUA) and Dompet Dhuafa, acting as a strategic partner. The program was prompted by a declining number of *amil* (religious service personnel) due to aging, a lack of facilities for corpse care, and low community participation in handling the deceased—particularly in modern residential areas. It employs a Participatory Action Research (PAR) methodology that integrates on-site education with practical training. Through this program, many community members have gained knowledge, confidence, and new skills and techniques; furthermore, the initiative has helped dispel gender-based taboos that often stigmatize women's involvement in the process of caring for the deceased.